2012
DOI: 10.1172/jci62110
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine 25–induced signaling suppresses colon cancer invasion and metastasis

Abstract: Chemotactic cytokines (chemokines) can help regulate tumor cell invasion and metastasis. Here, we show that chemokine 25 (CCL25) and its cognate receptor chemokine receptor 9 (CCR9) inhibit colorectal cancer (CRC) invasion and metastasis. We found that CCR9 protein expression levels were highest in colon adenomas and progressively decreased in invasive and metastatic CRCs. CCR9 was expressed in both primary tumor cell cultures and colon-cancer-initiating cell (CCIC) lines derived from early-stage CRCs but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 65 publications
(76 reference statements)
0
56
0
Order By: Relevance
“…The low proliferative activity of tumor-associated MAIT cells would speak against the possibility that increased intratumoral proliferation is a key mechanism for MAIT cell accumulation in the tumors. As invasive colon tumors produce more CCL20 and less CCL25 than do surrounding tissue (38,39), the CCL20/CCR6 axis might be more important than the CCR9/CCL25 axis in mediating MAIT cell recruitment to intestinal tumors. However, other factors such as endothelial adhesion molecules and additional chemokines are probably involved, as CCR6 expression MAIT cells have been implicated in defense against infectious diseases, but they have recently also been suggested to contribute to dysregulated mucosal immunity in systemic lupus erythematosus and inflammatory bowel disease (34,40).…”
Section: Discussionmentioning
confidence: 99%
“…The low proliferative activity of tumor-associated MAIT cells would speak against the possibility that increased intratumoral proliferation is a key mechanism for MAIT cell accumulation in the tumors. As invasive colon tumors produce more CCL20 and less CCL25 than do surrounding tissue (38,39), the CCL20/CCR6 axis might be more important than the CCR9/CCL25 axis in mediating MAIT cell recruitment to intestinal tumors. However, other factors such as endothelial adhesion molecules and additional chemokines are probably involved, as CCR6 expression MAIT cells have been implicated in defense against infectious diseases, but they have recently also been suggested to contribute to dysregulated mucosal immunity in systemic lupus erythematosus and inflammatory bowel disease (34,40).…”
Section: Discussionmentioning
confidence: 99%
“…Most notable is the case of CXCR4 in hematopoietic stem cells, which are kept within the bone marrow niche by the ligand CXCL12; a similar situation occurs in immature thymocytes retained in the thymic cortex by the CXCR4-CXCL12 axis (58). Another chemokine- receptor pair (CCL25-CCR9) was demonstrated to modulate colon cancer invasion and metastasis (59). CCL25 is expressed in the gastrointestinal microenvironment; when CCR9 + human CRC cells were systemically injected in the blood of immune-deficient mice, they formed orthotopic tumors, whereas CCR9 2 cells formed only extraintestinal tumors, suggesting that CCL25 retained CCR9 + neoplastic cells at primary tumor sites (59).…”
Section: Discussionmentioning
confidence: 99%
“…Another chemokine- receptor pair (CCL25-CCR9) was demonstrated to modulate colon cancer invasion and metastasis (59). CCL25 is expressed in the gastrointestinal microenvironment; when CCR9 + human CRC cells were systemically injected in the blood of immune-deficient mice, they formed orthotopic tumors, whereas CCR9 2 cells formed only extraintestinal tumors, suggesting that CCL25 retained CCR9 + neoplastic cells at primary tumor sites (59).…”
Section: Discussionmentioning
confidence: 99%
“…The natural ligand of CCR9, CCL25, is a thymusexpressed chemokine, which has been found primarily in the involvement of immune homeostasis and then in human solid tumors such as colorectal, prostate, ovarian, and breast cancers with relation to tumor invasion and metastasis (Singh et al, 2004;Svensson and Agace, 2006;Johnson-Holiday et al, 2011;Singh et al, 2011;Chen et al, 2012). However, the study of the CCL25/CCR9 axis on lung cancer is limited; so far, only one study has found that its expression correlated with aggressiveness and mediated key steps of metastasis in clinical samples and cell lines of NSCLC, especially in adenocarcinomas compared with squamous cell carcinomas, due to differential expression of matrix metalloproteinases and tissue inhibitor of metalloproteinases under the influence of CCL25 (Gupta et al, 2014).…”
Section: Ccl25/ccr9mentioning
confidence: 99%